Representações sociais sobre o acidente de trabalho em saúde - Medeiros Júnior, Antônio (2005)
The aim of the present study was to identify the representational elements of workrelated accidents in the health field, as well as investigate their most frequent occurrences at a university hospital, seeking to understand the cognitive, affective and social elements subjacent to the work process involved in health. The analysis focused on 470 middle and senior support staff of this hospital, based on the theoretical-methodological support of the Social Representations Theory. A combination of the following instruments was used for data collection: a free wordassociation test, a questionnaire, an interview and a field journal. Evoc 2000 software was used to identify representational structure. Chi-square and Mann-Whitney tests, at a significance level of 5%, were performed to verify the association between the independent variables and the occurrence of work accidents. In addition, thematic content analysis and lexicographic analysis by ALCESTE software program were used to understand textual content. It was observed that social representations of work-related accidents in the health area are centered in the contamination category, while the categories of prevention and professional unpreparedness are found peripherally. There was a significant association between the existence of multiple employment, the use of personal protective equipment (PPI) during work, job satisfaction and the occurrence of work accidents. The conclusions indicate that perforating-cutting occupational accidents predominated in the hospital and that the representations of the subjects intertwined, with a traditional discourse of work accidents strongly present in Occupational Health. It is therefore suggested that certain subjective aspects related to culture, in terms of controlling work accidents, such as: management, process, organization and the increasing precariousness